Development of social anxiety cognition scale for college students: Basing on Hofmann’s model of social anxiety disorder - Zha, Yuxin; Tang, Qin; Jin, Xiaoru; Cai, Xinfei; Gong, Wen; Shao, Yongcong; Weng, Xiechuan (Frontiers in Psychology, 2023)
Objective: To develop the Chinese version of the Social Anxiety Cognition Scale for College Students (SACS-CS) based on Hofmann's model of social anxiety disorder and examine its reliability and validity. Methods: Based on literature analysis and structured interviews, a theoretical model was constructed and behavioral examples were collected. According to the results of participants' and experts' evaluations, the initial SACS-CS was developed. The study data were collected from a total of 500 valid participants, randomly divided into two samples. Sample 1 (n = 200) and sample 2 (n = 300) were considered for exploratory factor analysis and confirmatory factor analysis (CFA), respectively. Internal reliability and validity were examined using all 500 participants, and temporal reliability was established using sample 3 (n = 70), who completed the scale again after four weeks. Results: The SACS-CS consists of 21 items, grouped under four factors: self-perception, social skills, emotional control, and cost estimation. The four-factor model fits well. The internal consistency coefficient of the scale and the four factors ranged from 0.87 to 0.96, and the test-retest reliability ranged from 0.76 to 0.84. The scores of the scale and the four factors were significantly correlated with the score of the Interaction Anxiousness Scale (r = 0.54–0.64). Conclusion: The SACS-CS possesses good reliability and validity and can be applied in the cognitive assessment of college students' social anxiety.